Molecular identification of adenovirus causing respiratory tract infection in pediatric patients at the University of Malaya Medical Center - Abd-Jamil, J.; Teoh, B.T.; Hassan, E.H.; Roslan, N.; AbuBakar, Sazaly (2010)
Background: There are at least 51 adenovirus serotypes (AdV) known to cause human infections. The prevalence of the different human AdV (HAdV) serotypes varies among different regions. Presently, there are no reports of the prevalent HAdV types found in Malaysia. The present study was undertaken to identify the HAdV types associated primarily with respiratory tract infections (RTI) of young children in Malaysia. Methods Archived HAdV isolates from pediatric patients with RTI seen at the University of Malaya Medical Center (UMMC), Kuala Lumpur, Malaysia from 1999 to 2005 were used. Virus isolates were inoculated into cell culture and DNA was extracted when cells showed significant cytopathic effects. AdV partial hexon gene was amplified and the sequences together with other known HAdV hexon gene sequences were used to build phylogenetic trees. Identification of HAdV types found among young children in Malaysia was inferred from the phylograms. Results At least 2,583 pediatric patients with RTI sought consultation and treatment at the UMMC from 1999 to 2005. Among these patients, 48 (< 2) were positive for HAdV infections. Twenty-seven isolates were recovered and used for the present study. Nineteen of the 27 (~70) isolates belonged to HAdV species C (HAdV-C) and six (~22) were of HAdV species B (HAdV-B). Among the HAdV-C species, 14 (~74) of them were identified as HAdV type 1 (HAdV-1) and HAdV type 2 (HAdV-2), and among the HAdV-B species, HAdV type 3 (HAdV-3) was the most common serotype identified. HAdV-C species also was isolated from throat and rectal swabs of children with hand, foot, and mouth disease (HFMD). Two isolates were identified as corresponding to HAdV-F species from a child with HFMD and a patient with intestinal obstruction. Conclusions HAdV-1 and HAdV-2 were the most common HAdV isolated from pediatric patients who sought treatment for RTI at the UMMC from 1999 to 2005. HAdV-B, mainly HAdV-3, was recovered from ~22 of the patients. These findings provide a benchmark for future studies on the prevalence and epidemiology of HAdV types in Malaysia and in the region.